Elevated IL-13Rα2 in intestinal epithelial cells from ulcerative colitis or colorectal cancer initiates MAPK pathway - Mandal, Debasmita; Levine, Alan D. (Inflammatory bowel diseases, 2010)
Background: Chronic inflammation in ulcerative colitis (UC) is a sizeable risk factor for colorectal cancer (CRC). Interleukin‐13 (IL‐13) is elevated in the UC mucosa and may induce dysregulated signaling in neighboring intestinal epithelial cells (IECs) and thus function as a tumorogenic cytokine. Methods: Expression of IL‐13 receptor chains on IECs obtained from control or chronically inflamed mucosa and colonic tumors was quantified by flow cytometry and immunoblot. IL‐13Rα1 and IL‐13Rα2 expression was significantly increased on IEC from UC and CRC patients compared to control and Crohn's disease (CD) subjects. Purified IEC from these subjects and cell lines expressing varying ratios of IL‐13Rα1 and IL‐13Rα2 chains were stimulated with IL‐13 in vitro to investigate by immunoblot the activation of the signal transducer and activator of transcription 6 (STAT6) and mitogen activated protein kinase (MAPK) signaling pathways. Results: Despite similarly elevated receptor expression in UC and CRC, IL‐13 does not activate the STAT6 or MAPK pathways in UC, while in colonic tumors only the STAT6 pathway is activated. Using neutralizing antibodies and cell lines expressing a range of surface densities for IL‐13Rα1 and IL‐3Rα2, we demonstrate that IL‐13Rα2 serves a dual role, initiating MAPK signaling at low concentrations and as an inhibitory, decoy receptor at high IL‐13Rα2 to IL‐13Rα1 ratios. Conclusions: IL‐13Rα2 is both a decoy receptor and induces MAPK signal transduction, depending on its relative expression and the local concentration of IL‐13, which together modulate the balance and intensity of the signaling pathways initiated in UC and CRC. Inflamm Bowel Dis 2010